(untitled) (Revista LIDER, 2018)
The study analyzes the mobility experiences, in Quillén and P.U.A, rural areas located in La Araucanía Region, Chile, of people living in rural areas, whose lives take place in precarious and isolated territories. This situation causes that people develop multiple mobility strategies to access different places during their daily commuting through rural and urban areas. The analysis showed a permanent migration to the city, collective mobility and lack of basic services, which conditions the inhabitants mobility strategies and their daily lives.